Chronic Lower Back Pain Among Hospital Workers: Effect of Ergonomic Chair Intervention on Quality of Working Life: A Literature Review - Khairunnisa, Zulfa (Writing Center IMERI FMUI, 2025)
Abstract Chronic lower back pain (CLBP) is a prevalent occupational problem among hospital workers, primarily caused by prolonged sitting and poor ergonomic posture. This condition contributes to reduced productivity, discomfort, and diminished quality of working life. Ergonomic chair interventions have been introduced as a potential preventive and therapeutic strategy to alleviate pain and improve workplace well-being. A narrative literature review was conducted by searching PubMed, Scopus, and Google Scholar databases from 2015 to 2025 using the keywords low back pain, chair intervention, and hospital workers. Selected studies discussed ergonomic chair modifications, posture correction, and work-related health outcomes. Most reviewed studies demonstrated that ergonomic chair interventions reduced pain intensity and disability scores, while improving posture stability and job satisfaction. Enhanced comfort and reduced fatigue were associated with better concentration and productivity. However, inconsistencies in chair design, user compliance, and study methods remain as limitations. A chair which is pivot adjustable and has adjustable backrest can reduce the muscle activity and also decreases the inter-vertebral disc pressure. Therefore, there is some support that adjustability of the chair can be directly associated with the function of the musculoskeletal system. Ergonomic chair interventions provide a promising approach to reducing CLBP and improving the quality of working life among hospital workers. Further high-quality studies are needed to develop standardized ergonomic recommendations for healthcare workplaces. Keywords: ergonomic chair, hospital worker, low back pain, quality of working life